The Possible Effects of High Vessel Traffic on the Physiological Parameters of the Critically Endangered Yangtze Finless Porpoise (Neophocaena asiaeorientalis ssp. asiaeorientalis) - Nabi, Ghulam; Hao, Yujiang; McLaughlin, Richard William; Wang, Ding (Frontiers in Physiology, 2018)
Background: Poyang is the largest freshwater lake in China, where the acoustic environment and space for the critically endangered Yangtze finless porpoises (YFPs) has been altered by heavy vessel traffic, and dredging activities. The density of vessel and the rate of dredging increases annually, especially in the area with the highest density of YFPs. The heavy vessel traffic can cause an increase in the physical activities and direct physical injuries to the YFPs. Furthermore, noise is a potent stressor to all cetaceans irrespective of age and can compromise all their physiological functions. The objective of this study was to examine the possible effects of heavy vessel traffic, and dredging on the biochemistry, hematology, adrenal, thyroid, and reproductive hormones of two different YFP populations. One population was living in Poyang Lake and the second living in the Tian-E-Zhou Oxbow which is a semi-natural resserve. Results: The results showed statistically significantly higher levels of serum cortisol, fT3, fT4, and lowered testosterone in both adult and juvenile YFPs living in Poyang Lake vs adult YFPs living in the Tian-E-Zhou Oxbow. The serum biochemical parameters (Aspartate Amino Transferase, Alkaline Phosphatase, High Density Lipoprotein cholesterol ratio, Globulin, Uric acid, Glucose, K+ and Amylase) and the hematology parameters (Red Blood Cells, Hematocrit, Mean Corpuscular Volume, White Blood Cells, and Eosinophils) were statistically significantly higher in the adult Poyang Lake YFPs vs adult Tian-E-Zhou Oxbow YFPs. On the other hand, adult males of the Tian-E-Zhou Oxbow also showed significantly higher levels of the serum biochemical parameters (Total Cholesterol, Light Density Lipoprotein cholesterol, Direct Bilirubin, Albumin, Lactate Dehydrogenase, CO2, and Na+) and the blood parameters (Mean Corpuscular Hemoglobin and Mean Corpuscular Hemoglobin Concentration). In Poyang Lake YFPs, various parameters showed significantly positive (fT4, amylase, neutrophil, Ca+2) or negative (total protein, lymphocyte) correlations with cortisol levels. Conclusions: The hyperactivity of adrenal glands in response to heavy vessel traffic and dredging resulted in significantly elevated cortisol levels in Poyang Lake YFPs. The higher cortisol level could possibly have affected various hormonal, hematological, and biochemical parameters, and ultimately the YFPs physiology. Keywords: Acoustic pollution, Cortisol, Critically endangered, Thyroid, Yangtze finless porpoise.